Hubungan Pola Asuh Orang Tua terhadap Kemandirian Personal Hygiene Anak Pra Sekolah - Marcellina Rasemi Widayanti; Irine Yunila Prastyawati; Lenda Yuliana Tlonaen (STIKes MERCUBAKTIJAYA, 2022)
Parenting is a combination of acceptance, response, rules and demands given by parents to their children and prepares their children to make decisions and act independently. The purpose of this study was to analyze the relationship between parenting patterns with the level of personal hygiene independence in preschool children. The population is the parents of Bunga Pertiwi Kindergarten students, with samples 30 mothers who meet the inclusion criteria, using purposive sampling technique. This research design uses a correlation study with a cross sectional approach. The data was processed using ASDPP. The result was that the majority (90%) of respondents applied democratic parenting and most (77%) of children were in the category of good personal hygiene. The results of the Spearman Rank test show that there is a positive relationship between parenting patterns and the personal hygiene independence of preschool children with p < (p = 0.000), correlation coefficient 0.636 with a high level of relationship. The application of democratic parenting to children will make children become independent personal hygiene. Therefore, the school can facilitate parents in introducing the best parenting styles for their children by conducting counseling in collaboration with professionals.